Charge delocalization in Z-isomers of (4α → 6”, 2α → 0 → 1”)-phenylflavans with R = H, OH and OCH3. Effects on bond dissociation enthalpies and ionization potentials - Lobayan, Rosana Maria (2013)
The (2 alpha-O-1´´)-bridged 4-phenylflavans comprise an interesting structure, included in natural antioxidants such as simple and dimeric A-type proanthocyanidins, catechins and condensed tannins. This work concerns the analysis of the stereoelectronic effects induced by substitution with R = H, OH and OCH3 in Z-isomers of (4alpha-6´´,2alpha- O-1´´)-phenylflavans using density functional methods in order to deepen the understanding of the molecular and structural properties of these compounds. A fully relaxed scan procedure was performed. A topological study of the molecular charge density (Bader theory, Atoms in Molecules) and a Natural Bond Orbital (NBO) analysis at the B3LYP/6-311++G** level were carried out. The stereochemistry of the molecules was discussed in detail focusing on the factors related to their antioxidant properties. Bond dissociation enthalpies (BDEs), ionization potentials (IPs) and electron affinities (EAs) were calculated for the lowest energy conformers. The Nuclear Magnetic Resonance (NMR) chemical shifts were also calculated at the B3LYP/6-31G** level, and compared with the earlier reported experimental values, showing that the thermodynamically most stable conformer is also the most stable kinetically. The effects of substituents on chemical shifts were quantified. Through a donor acceptor map a qualitative comparison among the studied compounds is given. The lower (higher) BDE (IP) values found for R = OH (4alpha-6´´,2alpha-O-1´´)-phenylflavans, were explained herein by specific mechanisms of charge delocalization. These findings highlight the key role played by hyperconjugative interactions in the stereoelectronic effects induced by substitution as an important factor in understanding the associated values of BDEs and IPs.